Natural convection characteristics of honeycomb fin with different hole cells for battery phase-change material cooling systems. (July 2022) - Liu, Fen; Wang, Jianfeng; Liu, Yiqun; Wang, Fuqiang; Chen, Yaping; Du, Qian; Sun, Fuzhen; Yang, Na
Abstract: As a nature production the lightweight honeycomb is used as a fin to increase the contact area with the PCM and improve its overall thermal conductivity. In this paper the effects of different honeycomb core shapes, sizes, and arrangements on melting under natural convection were investigated to determine the optimal honeycomb cell parameters. In this study, transient simulations based on VOF and enthalpy-porosity methods are developed, and the results show that compared with heat conduction, the melting time under natural convection conditions can be reduced. By analyzing different shapes, it is discovered that the melting effects of triangles, trapezoids, rectangles, and rhombuses are better than that of hexagons, the triangular melting time is reduced by 23.1%. The orthogonal experiments show that the ranking order of the effects on melting time and natural convection is Ra  > Shape > LHR. Furthermore, the optimal honeycomb hole core parameters are obtained from the analysis of a single factor. Compared with the hexagonal honeycomb fin, a battery's PCM with an optimal triangular honeycomb fin under natural convection exhibits a 23.3% increase in terms of temperature decrease. Highlights: Bionic honeycomb fin is used to heat transfer in PCM. Investigate the effects of different honeycomb core shapes, sizes, and arrangements under natural convection. Melting effect under natural convection is better than that under heat conduction. Temperature decrease of optimal honeycomb fin under natural convection increase by 23.3% compared with the hexagonal fin.